Recent Progress of Hybrid Solid‐State Electrolytes for Lithium Batteries - Liu, Xiaoyan; Li, Xinru; Li, Hexing; Wu, Hao Bin (Chemistry : a European journal, 2018)
Conventional liquid electrolytes for lithium batteries usually suffer from irreversible decomposition and safety concerns. Solid state electrolytes (SSEs) have been considered as the key for advanced lithium batteries with improved energy density and safety, whereas challenges remain for polymer and inorganic SSEs. Recently, hybrid solid‐state electrolytes (HSSEs) that integrate the merits of different electrolyte systems have been under intensive study. Herein, we summarize the recent progress of HSSEs with different compositions and structures. The design principle of each type of HSSEs are discussed, as well as their ionic conducting mechanism, electrochemical performance and effects of compositional/structural control. Finally, challenges and perspectives are provided for the future development of HSSEs and solid‐state lithium batteries. Hybrid solid‐state electrolytes (HSSEs) are keys to the development of lithium batteries with enhanced energy density and safety. This Minireview summarizes the recent development of HSSEs and discusses their design principles, performance and ionic conducting mechanism.